Antecedents and Consequences of Brand Trust for Pharmaceutical Drug Products - Falina Gunata; Pramono Hari Adi; Ary Yunanto (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The health industry potential in Indonesia is not optimal yet because of limited number of players in this industry (Kemenkes, 2017) even if health is an important factor. Based on the 2016 data of the Ministry of Health, there are 214 companies of Pharmaceutical Industry in Indonesia. Compared to total Indonesian population of about 257 million, this indicates the limited number of the industry players (detik.com accessed on March 18, 2019 at 21.00). To be attractive to the public, a business should have competitive advantage and consumers’ trust so as to attract consumers and make them willing to pay for what is offered and trust its brand. Consumers’ level of trust in brand of pharmaceutical products is lacking or often misguided (Rotfeld, 2009). Researches on brand trust in pharmaceutical products have not been conducted extensively and therefore result in difference between theory and field fact. The author studies brand trust in pharmaceutical products using the Consumer – Brand Characteristics variable as the indicator of Brand Image and Brand Personality, Brand Liking, Brand Experience, Brand Satisfaction, and Peer Support. According to (Matzler, 2016) Brand trust influences customer loyalty. 100 respondents are taken as the samples using a Purposive Sampling technique, which is based on certain criteria for maximum information. This research’s criteria are 21 to 60 years old non-health worker. The analysis employs SEM with software SPSS AMOS. The research concludes that Brand Image, Brand Personality, Brand Experience, Brand Satisfaction, and Peer Consumer influence Brand Trust, and Brand Trust influences consumer loyalty.